PENGARUH DER, ROI, CURRENT RATIO DAN RATA-RATA KURS TERHADAP UNDEPRICING PADA INITIAL PUBLIC OFFERING Studi Kasus Pada Perusahaan Non Keuangan di Indonesia - Ahmad, Gatot Nazir; Indriyanti, Isti; Buchdadi, Agung Dharmawan (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2013)
The purpose of this study is examining the effects of DER, ROI, current ratio, and exchange rate on underpricing of Initial Public Offering both simultaneously and partially. This study consist of two period, they are hot and cold market. The sample of hot market period are 42 companies while cold market are 25 companies. This study use Ordinary Least Square. The result of the regression shows that DER has a positive correlation in hot market period while in cold market period has not correlation. ROI has not correlation with underpricing either in hot market period nor cold market period. Current ratio has a positive correlation with underpricing in cold market period while in hot market period has not correlation with underpricing. Exchange rate has a positive correlation with underpricing in hot market period while in cold market has not correlation. For the simultan test, DER, ROI, current ratio, and exchange rates has a significant correlation on Î± = 10% with underpricing simultanly in hot market period, but in cold market period is not. Key words: underpricing, DER, ROI, current ratio, exchange rate